From rhetoric to action: Adapting the Act-Belong-Commit Mental Health Promotion Programme to a Danish context - Koushede, V.; Nielsen, L.; Meilstrup, C.; Donovan, Robert (The Clifford Beers Foundation, 2015)
In response to recent calls for implementing mental health promotion (MHP) in Denmark, the Danish National Institute of Public Health undertook a perusal of existing MHP frameworks. While a small number of such frameworks exist, the Act-Belong-Commit campaign that originated in Western Australia, was the only comprehensive, population-wide program identified that had a strong evidence base, demonstrated success in implementation and universal principles of well-being. Following a successful funding application to the Ministry of Health, the National Institute for Public Health, is leading a partnership to implement the Act-Belong-Commit campaign in Denmark in 2015–2017. This article describes the Act-Belong-Commit campaign and its implementation in Australia and how the National Institute of Public Health plans to introduce the campaign into Denmark. It is hoped that our planning for Denmark will be helpful to other countries planning to adopt the Act-Belong-Commit campaign.